Metal filled high density polyethylene composites: mechanical, electrical and thermal properties - Ahmad, Nurazreena (2006)
In this study, it was found that the mechanical the properties are affected by the shape and size of the filler, degree of crystallinity and the adhesion between metal fillers and polymer.